DETERMINANTS AFFECTING SURVIVAL OF SMES DURING COVID-19 PANDEMIC IN MANADO - Damongilala, Novia N.; Pangemanan, Sifrid S.; Tulung, Joy E. (FEB Universitas Sam Ratulangi Manado, 2021)
Food and Beverage industry right now hold the biggest share within SMEs sectors including in Manado; Food and Beverage industry as a whole is always evolving because of the trends within this industry. In the current situation; these businesses need to compete in an unprecedented condition. Not only they need to compete with each other but they also need to survive during the Covid-19 pandemic that already spread all across the world; it includes Indonesia and moreover Manado in this particular case. The purpose of this study is to find out the determinants that affect the survival of SMEs during the Covid-19 pandemic. This study uses a quantitative method and multiple linear regression as the tool of the research. The findings of this study show that the independent variables which are Business Resilience and Financial Technology simultaneously and independently affect the Survival of SMEs in Manado during COVID-19 Pandemic. From the results; there are several solutions offered for the problem such as Business incubator and the utilization of financial technology such as internet platform and e-commerce from leading company can act as one of the primary ways for the business to survive.Â Keywords: business resilience, financial technology, covid-19, survival of SMEs